2024
DOI: 10.3390/geotechnics4020026
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Utility of Large Language Models in Geotechnical Education and Problem Solving

Liuxin Chen,
Amir Tophel,
Umidu Hettiyadura
et al.

Abstract: The study explores the capabilities of large language models (LLMs), particularly GPT-4, in understanding and solving geotechnical problems, a specialised area that has not been extensively examined in previous research. Employing a question bank obtained from a commonly used textbook in geotechnical engineering, the research assesses GPT-4’s performance across various topics and cognitive complexity levels, utilising different prompting strategies like zero-shot learning, chain-of-thought (CoT) prompting, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…LLMs could potentially address these challenges by offering personalised learning experiences and adaptive content delivery, thus enhancing educational outcomes (Yang et al, 2024). Yet, the implementation of LLMs in this field faces significant hurdles, particularly in their ability to accurately integrate and apply domain-specific formulas and concepts, which are essential for solving specialised problems (L. Chen et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LLMs could potentially address these challenges by offering personalised learning experiences and adaptive content delivery, thus enhancing educational outcomes (Yang et al, 2024). Yet, the implementation of LLMs in this field faces significant hurdles, particularly in their ability to accurately integrate and apply domain-specific formulas and concepts, which are essential for solving specialised problems (L. Chen et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…The authors' previous study showed how the efficiency of GPT-4 can be improved by incorporating Chain of Thought (CoT) and our proposed custom instruction techniques. The authors showed that by utilising these two techniques, the accuracy of GPT-4 was improved from 29% to 34% and 67% for CoT and custom instruction, respectively (L. Chen et al, 2024). Despite these improvements, other development methods may offer unique benefits that enhance the effectiveness and reliability of AI-driven educational tools.…”
Section: Introductionmentioning
confidence: 99%